Analysis of Central Functions Provision in the Settlements of the West Herzegovina Canton - Putica Džajić, Jelena; Madžar, Danijela (Journal for Geography, 2023)
The provision of the settlement with central functions gives stimulation, and creates spatial, and social relations and processes within a certain space and population. This paper analyses the settlements' central function provision in West Herzegovina Canton. The settlement's centrality was determined based on the base groups of central functions: administration, education, health, supply, financial operations, post and telecommunications. After the collected and processed data, the settlements were classified into 4 categories of settlements based on the possession of certain functions; settlements without centrality, settlements with insufficient centrality, and settlements of the 3rd and 2nd rank of centrality. The research was conducted in September 2022 and developed model was applied, which is based on the quantitative procedure of evaluating the settlement's centrality.